The authority of Khalwatiyah Tariqa of Sheikh Yusuf Al-Makassary on fostering religious moderation in South Sulawesi - Azis, Aminah; Pabbajah, Mustaqim; Hannani,; Pabbajah, M. Taufiq Hidayat (Penerbit Universiti Kebangsaan Malaysia, 2024)
Religious moderation as an effort to cultivate a moderate attitude within the diversity of society has been exempli9ied by Khalwatiyah Tariqa Syekh Yusuf Al-Makassary (KTSYA). This study elucidates the existence of KTSYA in building and nurturing religious moderation in socio-religious practices. It relies on a qualitative descriptive approach where data were collected through observations, interviews with KTSYA key 9igures and adherents, and analysis of relevant literature. Authority and religious moderation were used as concept-based analyses. This current study presents three main 9indings, i.e., KTSYA’s teaching conceptualization in socio-religious life; KTSYA’s teaching as the basis of values understanding of religious moderation driven from moderate, inclusive, and humanistic approaches; KTSYA utilizes four aspects of religious moderation: national commitment, tolerance, non-violence, and local cultural practices accommodation. This study asserts that KTSYA is not just a Su9i community associated with divine teaching but also potential teaching to foster religious moderation through practical religious involvement in government and societal activities. This study af9irms the signi9icance of accommodating Su9i’s teachings to promote and build moderate attitudes in global world.